Integrasi Pembelajaran Berbasis Masjid dalam Meningkatkan Karakter Islami Siswa - Setiyo Nuhari (PT PUSTAKA CENDEKIA GROUP, 2025)
Islamic character education is a fundamental aspect of the national education system, especially in facing the challenges of moral degradation in the modern era. One approach that is considered effective in shaping students' character is through the integration of mosque-based learning that combines formal education with strengthening Islamic values ​​contextually. This study aims to systematically examine how mosque-based learning can improve students' Islamic character and explore the forms, strategies, and challenges of its implementation in various educational institutions. The method used is a systematic literature review by examining journal articles, books, proceedings, and relevant scientific documents published between 2015 and 2025. The analysis was carried out through keyword identification, literature selection with inclusion and exclusion criteria, and thematic synthesis of relevant findings. The results of the study indicate that mosque-based learning is effective in improving religious understanding, worship practices, and the formation of students' social and spiritual character. Programs such as TPA, youth mentoring, and routine studies have a significant role in the process of internalizing Islamic values. However, this integration still faces challenges such as the lack of synergy between schools and mosques and differences in curriculum approaches. Therefore, active collaboration between teachers, community leaders, and parents is needed to create a sustainable Islamic character education ecosystem. These findings provide direction for the development of educational policies and practices based on religious and contextual values ​​in Indonesia.